Chemical changes in almonds throughout storage: modeling the effects of common industry practices. (22nd February 2019) - Parrish, Daniel R.; Pegg, Ronald B.; Kerr, William L.; Swanson, Ruthann B.; Huang, Guangwei; Kerrihard, Adrian L.
Summary: Further investigations of almond degradation under typical industrial storage conditions from a quantitative perspective are warranted. This study modeled effects of packaging, temperature (TEMP), relative humidity (RH) and roasting on chemical attributes of almonds stored according to common industry practices throughout 16 months. Roasted samples were stored in high‐barrier bags (HBB) or polypropylene bags (PPB) at multiple combinations of TEMP and RH. Raw samples were held in unlined cardboard cartons (UC) or PPB under the same conditions. Almonds were assessed bimonthly for oxidation products, free fatty acids, moisture content and water activity. Results indicated roasting almonds improved quality preservation. Models showed HBB (rather than PPB) to provide benefits to stability comparable to reductions in storage TEMP of ~15 to 30 °C. PPB (rather than UC) showed benefits to peroxide formation of similar magnitude. Our data shows HBB to be a superior packaging choice, and UC to associate with the greatest rates of degradation. Abstract : Raw and roasted almonds were stored for 16 months in numerous packaging materials and within differing conditions of humidity and temperature. Degradation was assessed throughout and modeled according to storage conditions. Roasting, low storage temperature and high barrier bags were shown to improve shelf life.